Design Strategies for Structurally Controlled Polymer Surfaces via Cyclophane‐Based CVD Polymerization and Post‐CVD Fabrication. Issue 37 (9th August 2022) - Hassan, Zahid; Varadharajan, Divya; Zippel, Christoph; Begum, Salma; Lahann, Jörg; Bräse, Stefan
Abstract: Molecular structuring of soft matter with precise arrangements over multiple hierarchical levels, especially on polymer surfaces, and enabling their post‐synthetic modulation has tremendous potential for application in molecular engineering and interfacial science. Here, recent research and developments in design strategies for structurally controlled polymer surfaces via cyclophane‐based chemical vapor deposition (CVD) polymerization with precise control over chemical functionalities and post‐CVD fabrication via orthogonal surface functionalization that facilitates the formation of designable biointerfaces are summarized. Particular discussion about innovative approaches for the templated synthesis of shape‐controlled CVD polymers, ranging from 1D to 3D architecture, including inside confined nanochannels, nanofibers/nanowires synthesis into an anisotropic media such as liquid crystals, and CVD polymer nanohelices via hierarchical chirality transfer across multiple length scales is provided. Aiming at multifunctional polymer surfaces via CVD copolymerization of multiple precursors, the structural and functional design of the fundamental [2.2]paracyclophane (PCP) precursor molecules, that is, functional CVD monomer chemistry is also described. Technologically advanced and innovative surface deposition techniques toward topological micro‐ and nanostructuring, including microcontact printing, photopatterning, photomask, and lithographic techniques such as dip‐pen nanolithography, showcasing research from the authors' laboratories as well as other's relevant important findings in this evolving field are highlighted that have introduced new programmable CVD polymerization capabilities. Perspectives, current limitations, and future considerations are provided. Abstract : Design strategies for structurally controlled polymer surfaces via cyclophane‐based chemical vapor deposition (CVD) polymerization with precise control over chemical functionalities, and post‐CVD fabrication via orthogonal surface functionalization that facilitates the formation of designable biointerfaces are summarized. Particular discussion about CVD copolymerization for multifunctional surfaces, and templated‐synthesis of structurally controlled CVD polymers, ranging from 1D to 3D architecture is provided.